2000
DOI: 10.1128/jvi.74.16.7691-7693.2000
|View full text |Cite
|
Sign up to set email alerts
|

Initial Interactions of Subgenus D Adenoviruses with A549 Cellular Receptors: Sialic Acid versus α v Integrins

Abstract: Selected members of the adenovirus family have been shown to interact with the coxsackie adenovirus receptor, αvintegrins, and sialic acid on target cells. Initial interactions of subgenus D adenoviruses with target cells have until now been poorly characterized. Here, we demonstrate that adenovirus type 8 (Ad8), Ad19a, and Ad37 use sialic acid as a functional cellular receptor, whereas the Ad9 and Ad19 prototypes do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
140
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 154 publications
(149 citation statements)
references
References 20 publications
9
140
0
Order By: Relevance
“…Cells were rinsed with phosphate-buffered saline (PBS) and fixed with 3% (wt/vol) paraformaldehyde in PBS for 20 min at room temperature. After quenching aldehyde groups with 50 mM NH 4 Cl and 20 mM glycine in PBS, cells were permeabilized with 0.2% saponin in PBS with 5% FCS to block nonspecific binding. The cells were incubated with the primary antibody diluted in 0.2% saponin-5% FCS in PBS for 1 h at room temperature, washed four times in the above buffer without FCS, and incubated with the secondary antibody (fluorescein-or rhodamine-conjugated goat or donkey anti-mouse, anti-rabbit, or anti-sheep immunoglobulin G, respectively; Dianova, Hamburg, Germany) for 1 h. After four further washing steps the coverslips were mounted on glass slides with Histogel (Linaris, Wertheim-Bettingen, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were rinsed with phosphate-buffered saline (PBS) and fixed with 3% (wt/vol) paraformaldehyde in PBS for 20 min at room temperature. After quenching aldehyde groups with 50 mM NH 4 Cl and 20 mM glycine in PBS, cells were permeabilized with 0.2% saponin in PBS with 5% FCS to block nonspecific binding. The cells were incubated with the primary antibody diluted in 0.2% saponin-5% FCS in PBS for 1 h at room temperature, washed four times in the above buffer without FCS, and incubated with the secondary antibody (fluorescein-or rhodamine-conjugated goat or donkey anti-mouse, anti-rabbit, or anti-sheep immunoglobulin G, respectively; Dianova, Hamburg, Germany) for 1 h. After four further washing steps the coverslips were mounted on glass slides with Histogel (Linaris, Wertheim-Bettingen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the ␣2 domain of major histocompatibility complex (MHC) class I molecules, expressed in all nucleated cells, was proposed as a low-affinity receptor for Ad5 (15,30). Interestingly, while the subgenus D Ads Ad9, Ad15, and Ad19p were shown to attach to CAR (57), the EKC-causing members of subgenus D, Ad8, Ad19a, and Ad37, seem to utilize ␣(233)-linked sialic acid but not CAR (3,4). Although striking, this common feature of EKC-causing Ads cannot explain their distinct pathogenesis in the eye, since sialic acid is expressed on virtually all cell types of the body.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been demonstrated that all EKCcausing adenoviruses use sialic acid-containing oligosaccharides as cellular receptors instead of CAR (3,4,5). This usage matches the unique pathogenicity of the EKC-causing adenoviruses (Ad8, Ad19a, and Ad37).…”
mentioning
confidence: 99%
“…These three are closely related to HAdV-8, HAdV-19a and HAdV-37, and they all belong to species D (Hiroi et al 2013). Sialic acid is a known, functional receptor for HAdV-8, HAdV-19a and HAdV-37 (Arnberg et al 2000), and as the sialic acid-interacting knob domains of the fibre protein of HAdV-53, HAdV-54 and HAdV-56 are closely homologous to those of personal communication), it is likely that these species also use sialic acid as a cellular receptor. For patients with sialic receptor, the adenovirus viral load was higher at visit 1.…”
mentioning
confidence: 99%